TEACHING ENGLISH AS A BRIDGE TO INTERCULTURAL UNDERSTANDING IN MULTILINGUAL CLASSROOMS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
In this article, it is discussed that contemporary English language teaching (ELT) can and should function as a deliberate bridge to intercultural understanding in multilingual classrooms. Moving beyond narrow language skills, teachers who foreground intercultural competence prepare learners to communicate across cultural boundaries, negotiate meaning with speakers of diverse English varieties, and reflect critically on their own and others’ cultural assumptions.